(untitled) (Pedagogy of Higher and Secondary Education, 2014)
Khrebtova V. V. The development of the ideas of multicultural education in the context of international experience. The problem of the origin and perspectives of the development of multicultural education is elucidated, the position of the investigated issue in the modern pedagogics is analysed, the general pedagogic question of the essence of multicultural education is characterized and the specificity and principal stages of the development of multicultural education in compliance with the new educational paradigm are defined in the article.